Transplantation of Horseshoe Kidney from Living, Genetically Unrelated Donor. (9th July 2015) - Kikkawa, Kazuro; Wakamiya, Takahito; Kusumoto, Hiroki; Matsumura, Nagahide; Kohjimoto, Yasuo; Hara, Isao
Abstract : We report a case of renal transplantation using a horseshoe kidney from a living, genetically unrelated donor. The recipient was a 60-year-old man with diabetic nephropathy, and the donor was the 63-year-old wife of the recipient with a horseshoe kidney free of complications. Computed tomography showed two renal arteries and one renal vein on the left side, and the isthmus was perfused by several accessory arteries and veins. To demarcate the boundary of the isthmus, the left renal artery was ligated and cannulated for in situ perfusion. Furthermore, the isthmus was clamped, and the boundary of the isthmus was confirmed. The kidney was divided at the left margin of the perfused boundary. The cut ends of the isthmus were closed by sutures. The left kidney was transplanted into the right iliac fossa of the recipient. Asymptomatic fluid collection occurred on the cut surface at the isthmus of the donor, and this fluid decreased in due course. On the other hand, the recipient experienced no surgical complication or rejection, while maintaining serum creatinine levels of 2.00–2.20 mg/dL over a 22-month follow-up period. Horseshoe kidneys may be used for transplantation in selected cases after a detailed preoperative evaluation.